Sequence-Defined Transposon Mutant Library of Burkholderia thailandensis - Larry A. Gallagher (American Society for Microbiology, 2013)
ABSTRACT We constructed a near-saturation transposon mutant library for Burkholderia thailandensis, a low-virulence surrogate for the causative agent of melioidosis (Burkholderia pseudomallei). A primary set of nearly 42,000 unique mutants (~7.5 mutants/gene) was generated using transposon Tn5 derivatives. The strains carry insertions in 87% of the predicted protein-coding genes of the organism, corresponding to nearly all of those nonessential for growth on nutrient agar. To achieve high genome coverage, we developed procedures for efficient sequence identification of insertions in extremely GC-rich regions of DNA. To facilitate strain distribution, we created a secondary library with two mutants per gene for which most transposon locations had been confirmed by resequencing. A map of mutations in the two-allele library and procedures for obtaining strains can be found at http://tools.nwrce.org/tn_mutants/ and http://www.gs.washington.edu/labs/manoil/. The library should facilitate comprehensive mutant screens and serve as a source of strains to test predicted genotype-phenotype associations. IMPORTANCE The Gram-negative bacterium Burkholderia pseudomallei is a biothreat agent due to its potential for aerosol delivery and intrinsic antibiotic resistance and because exposure produces pernicious infections. Large-scale studies of B. pseudomallei are limited by the fact that the organism must be manipulated under biological safety level 3 conditions. A close relative of B. pseudomallei called Burkholderia thailandensis, which can be studied under less restrictive conditions, has been validated as a low-virulence surrogate in studies of virulence, antibiotic resistance and other traits. To facilitate large-scale studies of B. thailandensis, we created a near-saturation, sequence-defined transposon mutant library of the organism. The library facilitates genetic studies that identify genotype-phenotype associations conserved in B. pseudomallei.